2015
DOI: 10.1016/j.vaccine.2015.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in immune response to vaccination: A participant-level meta-analysis of randomized trials of IMVAMUNE ® smallpox vaccine

Abstract: Introduction Previous research shows immune response to vaccination differs by sex but this has not been explored for IMVAMUNE®, a replication-deficient smallpox vaccine developed in response to the potential for bioterrorism using smallpox. Methods We conducted a participant-level meta-analysis (N=275, 136 men, 139 women) of 3 randomized trials of IMVAMUNE conducted at 13 centers in the US through a federally-funded extramural research program. Studies were eligible for inclusion if they tested the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Gender was significantly associated with vari-ations in Nt antibody development after smallpox vaccination, with female shaving a significantly higher Nt antibody titer than males [22]. On the other hand, Troy et al, reported higher PRNT titers in men after vaccination [23]. In our study, Nt antibody titer between males and females were similar.…”
Section: Discussionsupporting
confidence: 60%
“…Gender was significantly associated with vari-ations in Nt antibody development after smallpox vaccination, with female shaving a significantly higher Nt antibody titer than males [22]. On the other hand, Troy et al, reported higher PRNT titers in men after vaccination [23]. In our study, Nt antibody titer between males and females were similar.…”
Section: Discussionsupporting
confidence: 60%
“…Most of the other immune outcomes also exhibited a reduced response, but the reduction did not meet statistical significance (e.g., IL-2 secretion reduced by 50%: p=0.055). As noted earlier, we and others have described sex-based differences in humoral immunity to smallpox vaccination [30,36,37]. Sex differences have also been noted for numerous other vaccines as well [38, 39] and is an important factor that deserves to be studied in greater detail and taken into account when developing vaccination schedules and dosage recommendations, evaluating adverse event rates, and when planning clinical trials of new vaccines.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, when using the 23-valent pneumococcal polysaccharide vaccine (PPV23), vaccine efficacy was higher in females versus males [21]. In contrast to the above studies, men demonstrated superior Ab responses to diphtheria, measles, and smallpox vaccines when compared to women [19,22]. Men were also better protected against diphtheria and tetanus than their female counterparts [23,24].…”
Section: Introductionmentioning
confidence: 99%